Pengaruh Kinerja Keuangan, Ukuran Perusahaan Dan Opini Audit Terhadap Harga Saham Pada Perusahaan Sub Sektor Properti - Shinta Dewi Astari; Edi Sihotang; Sabam Hutajulu (Program Studi Akuntansi Sekolah Tinggi Ilmu Ekonomi Tri Bhakti, 2022)
Before carrying out investment activities, usually potential investors will choose stocks that can provide optimal returns. Financial reports are a source of information that can be used by potential investors in making investment decisions. The purpose of this research is to fnd out the influence of financial performance which is proxy through Return on Assets, firm size and audit opinions on stock prices. The sample collection technique has been carried out by using purposive sampling method. The samples are 20 property companies which are listed in Inonesian Stock Exchange (IDX) in 2016-2018 periods. This research test shows that simultaneoulsy financial performance, firm size and audit opinions give influence the stock price of property companies which are listed in Indonesia Stock Exchange in 2016-2018 periods.